PENGARUH SOFT TQM TERHADAP KINERJA PERUSAHAAN DENGAN HARD TQM SEBAGAI VARIABEL MODERATING PADA PERHOTELAN DI PURWOKERTO - Tri Sekar Priyanti (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This research is to develop a theoritical model about performance and to do an empirical test to know the influence of soft TQM toward performance with Hard TQM as moderating by empirical test in medium hotel service company in Purwokerto. The research subject is CEO. The research population is 115 melati hotel service companies in Purwokerto. The research sample is 90 melati hotel service companies determined by SPSS for windows with Moderating Regresion Analysis. The conclution of the research are: Soft TQM ( includes Leadership, Customer focus, People Management) and Hard TQM have a positive influence in improving the performance of the company so the management of hotel service needs to consider policies related to soft and hard TQM. Hard TQM moderate the soft TQM on the performance of the company so that the management needs to considers policies related to the hard TQM effort that can be done to support procees management, planning, and information system. The implication of the research are: This study theoritically based and support the Malcolm Baldrige model of the soft and hard TQM and company performance. Specifically the result of this research may help to the hospitality business to always do quality repairs with a TQM.. Limitation of this study include: the number of companies involved in this research is still considered small. Researchers use only the perception of corporate leaders in answering the questionaire. Keyword: Soft TQM, Hard TQM, Performance